Plant Based Biosynthesis of Copper Nanoparticles and its Efficacy on Seed Viability and Seedling Growth in Peanut (Arachis hypogaea Linn.) - Lakshmi Tulasi, S.; Swamy, A.V.V.S.; Peddi, Pavani; Usha Rani, N. (Asian Journal of Chemistry, 2022)
Nano-fertilizers can easily adsorb into the plant and can increase the reactive points in the plant and hence are treated as an efficient alternative to the conventional fertilizers. Based on this, the present study was intended to synthesize copper nanoparticles (CuNPs) using aqueous root extract of Schrebera swietenioides Roxb. as green reducing agent. The synthesized nanoparticles were studied for its effectiveness on enhancement of seed germination and plant growth promotion on peanut (Arachis hypogaea Linn.). The formation of nanoparticles was confirmed by observing colour change in the reaction mixture, which shows characteristic absorption maxima at 340 nm. The SEM and TEM analysis confirmed that the nanoparticles were in monodispersed with spherical to irregular shape with an average particle size of 35 nm. The EDX analysis confirmed that the nanoparticles contain 82.5% copper metal. The synthesized nanoparticles were applied for its seed germination enhancement activity on peanut seeds and results confirms that the nanoparticles were significantly enhances the germination of peanut seeds with decrease in mean germination time. The peanut plant growth also enhances when compared with metal solution treatment and untreated plants. The root length of CuNPs treated plants was observed to be 9.27 ± 0.15 cm, which is significantly more than the untreated (6.40 ± 0.10 cm) as well as treated copper metal (7.13 ± 0.25 cm) plants. The shoot length of 19.13 ± 0.20 cm was observed for nano-treated plants and is greatly enhanced than the untreated (10.30 ± 0.20 cm) and treated copper metal (11.27 ± 0.25 cm) plants. The protease activity on day 5 of the germination study was found to be 0.904 ± 0.004, 0.133 ± 0.002 and 0.095 ± 0.002 units/mL, respectively for the peanut seeds treated with CuNPs, copper metal solution and untreated conditions. The catalase activity at 5th day of seed germination studies the activity was observed to be 45.177 ± 0.192, 23.691 ± 0.074 and 18.331 ± 0.209 units/min/g, respectively for CuNPs treated, copper sulphate treated and untreated pea nut seeds. The water update of the nano treated seeds was observed to be very high along with high quantity of photosynthetic pigments when compared with the other treatments in the study. Based on the results achieved, it can be confirmed that the nano-treatment enhances the seed germination and plant growth promotion on peanut seeds.